FORMULATION OF NATIONAL RESILIENCE POLICY TOWARDS THE INSTITUTIONALIZED MULTICULTURAL TRADITION IN ORGANIZING HARMONIOUS RELATIONS BETWEEN ETHNICITYSCOPUS JOURNAL - Roni Lukum; Rauf Hatu; Sastro Wantu; Ismet Sulila; Yanti Aneta (INJOSEDU: International Journal of Social and Education, 2025)
Diversity background behind ideology, religion , ethnicity , race citizens can just become potential conflict social when No managed with well , therefore required formulation policy resilience proper national in to organize ethnic groups in Indonesia, especially for areas that are used as as area objective policy macro in placement transmigration . Why thus when No There is caution in manage policy resilience national to placement transmigration will cause turbulence social in the area with resident local as in the area regency Boalemo as one of the location placement transmigration in Gorontalo Province. Research purposes This is For know formulation policy resilience national to institutionalization tradition multiculturalism in to organize connection harmonious between ethnicity in the Regency Boalemo Province Gorontalo, revealing supporting factors success implementation formulation policy resilience national to institutionalization tradition multiculturalism in to organize connection harmonious between ethnicity in the Regency Boalemo Province Gorontalo, for see implications formulation policy resilience national to institutionalization tradition multiculturalism in to organize connection harmonious between ethnicity in the Regency Boalemo Gorontalo Province. Disclosure objective study This used with method study qualitative. Findings study can concluded that (1). Formulation Policy resilience national in institutionalize tradition multiculturalism in planning diversity ethnic groups in the Regency via Communication Forum between people religious (FKUB) as implementation policy macro government center Still in very tough condition in realize integration national , (2 ) supporting factors success formulation policy resilience national to institutionalization tradition multiculturalism in to organize connection harmonious between ethnicity caused by wisdom local and role institution formal education (3). Impact formulation policy resilience national to institutionalization tradition multiculturalism in to organize connection harmonious between ethnicity in the Regency Boalemo Gorontalo Province has give contribution to stability security , stability economy , stability politics and stability social so that has increase growth economy government area regency Boalemo as consequence from contribution inhabitant transmigration in various sector business agriculture , livestock , crafts , sector business trading from inhabitant ethnic origin from inhabitant transmigration .